Iterated boolean sums of Bernstein and related operators - Raşa, Ioan (Rev. Anal. Numér. Théor. Approx., 2006)
Let \((T(t))_t≥0\) be the semigroup associated with the classical Bernstein operators \((B_n)_n≥1\) on \(C[0,1]\). We obtain rates of convergence for iterated boolean sums of the operators \(T( 1n) .\)